Correction: Pain-related fear of movement dynamics in individuals with and without low back pain participating in weightlifting and/or powerlifting training. - Bernard X W Liew; Josce Syrett; Paul Freeman; David W Evans (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0276983.].